Global supply chain ecosystems : strategies for competitive advantage in a complex world - Millar, Mark (Supply Chain Consultant) (London ; Philadelphia : Kogan Page, 2015)
"With increased globalization, off-shoring, and outsourcing, global supply chain management is becoming an important issue for many businesses. Global supply chain management shares some of the main concerns of traditional supply chain management, such as lowering the costs of procurement and decreasing the risks related to purchasing activities. It also has the additional challenge of involving a company's worldwide interests and suppliers, covering numerous organizations across several countries, borders, time zones, cultures, and languages. Global Supply Chain Ecosystems explores the latest market trends and industry developments across emerging, developing, and developed markets. Author Mark Millar presents practical insights that will help companies capitalize on market opportunities, overcome supply chain challenges, and make better informed business decisions. In addition to highlighting key supply chain shifts such as the move beyond globalization back towards regionalization, the book explains several critical aspects of global supply chain ecosystems, including visibility, risk, resilience, sustainability, and collaboration"--
"Twenty-first-century supply chains have evolved into world-wide inter-connected supply-and-demand networks comprising vastly more complex operations, with profound inter-dependencies and exposure to greater volatility in our uncertain world. The linear concept of a chain is therefore no longer adequate to describe these complex international networks of suppliers, stakeholders, partners, regulators and customers that are involved in ensuring the efficient and effective movement of products, services, information and funds around the world - we are firmly in the era of Global Supply Chain Ecosystems. Exploring the latest market trends and industry developments across emerging, developing and developed markets, in Global Supply Chain Ecosystems industry leader Mark Millar presents detailed and practical insights that will help you capitalise on market opportunities, overcome supply chain challenges and make better informed business decisions. In addition to highlighting key supply chain shifts such as the move beyond globalisation back towards regionalisation, this ground-breaking new publication explores several critical aspects of global supply chain ecosystems - including visibility, resilience, sustainability and collaboration"--
Includes bibliographical references (pages 255-263) and index.
Keywords: Business logistics; BUSINESS & ECONOMICS / Purchasing & Buying; BUSINESS & ECONOMICS / Production & Operations Management; BUSINESS & ECONOMICS / International / General; BUSINESS & ECONOMICS / Distribution; BUSINESS & ECONOMICS / Management